ANALYSIS OF GRAIN PRODUCTION IN THE REPUBLIC OF KAZAKHSTAN AND PROSPECTS FOR ENSURING FOOD SECURITY - Alexander TSYPIN; Alla VAVILINA; Tatiana KOMAROVA; Anna FIRSOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The relevance of this study is due to the growing role of agriculture in the economic development of systems and the need to analyze and develop approaches to improving the efficiency of agriculture and ensuring food security of the each country. The object of this study is the grain production in Kazakhstan based on retrospective statistics and within the framework of the prospects for ensuring food security. To achieve this goal, the following methods were used: analysis, synthesis, comparison, historical and complex mathematical and statistical methods. The following can be cited as the main results of the study: at the end of 2022, Kazakhstan was not among the top ten leaders in the world's gross wheat harvest, possessing only 2% of the global figure, while it ranks 8th in exports with 3.4% of the world value. Retrospective dynamics of the gross grain harvest in Kazakhstan shows that until 1980 there was an increase in its levels, then a fall until 1998, which again changed to growth, but the levels reached during the Soviet period of development have not been exceeded at present. The main grain-producing regions are concentrated in the northern part of Kazakhstan, which is due to acceptable natural and climatic conditions and the presence of chernozems. Directions for modernizing Kazakhstan's agriculture are presented, which will ensure its food security.